Investigation on the failure mechanism of the collapse of the columnar jointed basalt in underground cavern - Zhao, Jin-Shuai; Zhang, Jian-Cong; Pei, Shu-Feng; Xing, Liang; Chen, Chong-Feng; Zhang, Guang-Duan (Frontiers in Earth Science, 2024)
Columnar jointed basalt (CJB) is a kind of jointed rock with a polygonal cylinder mosaic structure that has complex mechanical properties such as discontinuity and heterogeneity. The typical geological structure of the CJB is the intercolumnar joint plane and the implicit joint plane, which obviously affect the mechanical properties of the rock mass. Controlling the unloading relaxation of the CJB is a key problem during the construction of underground engineering. In this paper, in-situ acoustic wave and panoramic borehole camera measurements were carried out in the cavern of the Baihetan project to understand the failure mechanism of the collapse of the CJB. It was quite clear that the evolution of the excavation damage zone (EDZ) of the CJB depends on the time and spatial effects. The closer to the collapse zone, the greater the degree of relaxation failure of the columnar joint rock mass; the further away from the cavern perimeter, the more stable the surrounding rock. The correction between wave velocity and cracks in the rock mass was also discussed. This field test and theoretical analysis can provide a reference for studying the failure mechanism and control measures of CJB in underground caverns under high geostress.